Afrotropical Melambiina: revision of the genus Tragardhus Koch, 1956 and redescription of Pseudemmallus Koch, 1956 (Tenebrionidae: Pedinini) - Kamiński, Marcin Jan (Zootaxa, 2017)
The genus Tragardhus Koch, 1956 (Pedinini: Melambiina) is revised to include nine Afrotropical species, five of which are new. A taxonomic treatment of the genus is provided including a morphological study, new species descriptions, keys, illustrations, and notes on species distributions. The following species are included: Tragardhus (Mitragardhus) nodosus Koch, 1956, T. (M.) ewae sp. nov., T. (M.) ryszardi sp. nov., T. (M.) zuzannae sp. nov., Tragardhus (Tragardhus) biapicalis Koch, 1956, T. (T.) glandipleurum Koch, 1956, T. (T.) jani sp. nov., T. (T.) majae sp. nov. and T. (T.) stigmaticus Koch, 1956. Additionally, a monotypic genus Pseudemmallus Koch, 1956, previously known from a single specimen representing P. aspericollis Koch, 1956, is redescribed based on newly available material.